Impact of compost to produce rice-wheat crops from saline sodic soil - Sarwar, Ghulam; Schmeisky, Helge; Hussain, Nazir; Malik, Muhammad Ashraf; Manzoor, Muhammad Zeeshan; Zafar, Ayesha; Murtaza, Ghulam (Journal of Pure and Applied Agriculture, 2023)
A significant area of Pakistan is affected by high concentration of soluble and exchangeable salts that limit crop production. So, this study was planned to thrash positive effects of compost not only on yield of rice and wheat plants, but also on its role as a recovery agent. To achieve this purpose, a salt sodium field with pH = 8.63, TSS = 49.5 me L-1 , SAR = 18.99 was selected. Experiment consisted of 6 treatments that were repeated four times using a randomized complete block design.